2006
DOI: 10.1128/jvi.80.2.759-768.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane-Destabilizing Peptide in Capsid Protein L2 Is Required for Egress of Papillomavirus Genomes from Endosomes

Abstract: Papillomaviruses are internalized via clathrin-dependent endocytosis. However, the mechanism by which viral genomes pass endosomal membranes has not been elucidated. In this report we show that the minor capsid protein L2 is required for egress of viral genomes from endosomes but not for initial uptake and uncoating and that a 23-amino-acid peptide at the C terminus of L2 is necessary for this function. Pseudogenomes encapsidated by L1 and L2 lacking this peptide accumulated in vesicular compartments similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
171
2
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 53 publications
4
171
2
7
Order By: Relevance
“…Virion binding leads to a conformational change in the capsid that in turn permits furin to cleave the N terminus of L2, which may occur at the cell surface or within an early endosomal compartment. The capsid undergoes uncoating in a late endosomal compartment, leading to furin-cleaved L2 and the associated genome to escape from the endosome into the cytoplasm via a mechanism that also involves the C terminus of L2 (6). Furin inhibition by dec.-RVKR-cmk prevents the escape of L2 and the genome from the endosome but does not appear to interfere with virion trafficking or uncoating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virion binding leads to a conformational change in the capsid that in turn permits furin to cleave the N terminus of L2, which may occur at the cell surface or within an early endosomal compartment. The capsid undergoes uncoating in a late endosomal compartment, leading to furin-cleaved L2 and the associated genome to escape from the endosome into the cytoplasm via a mechanism that also involves the C terminus of L2 (6). Furin inhibition by dec.-RVKR-cmk prevents the escape of L2 and the genome from the endosome but does not appear to interfere with virion trafficking or uncoating.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of the genome to the transcriptionally active nuclear domain 10, which is critical to the efficient establishment of infection, depends on L2. It has also been demonstrated that a C-terminal region of L2 mediates endosomal escape after viral uncoating (6). Additionally, a recent report showed that L2 interacts with syntaxin 18 during entry and possibly uses this resident endoplasmic reticulum protein as a tether for transport toward the nucleus (7).…”
mentioning
confidence: 99%
“…Both viruses have recently been shown to carry membrane-destabilizing domains within their capsid structural proteins (67,69). Because defensins are known to interact with membranes, it is possible to imagine that they act against papillomaviruses and adenoviruses by interacting with cellular membranes in a manner that blocks the effects of membrane-destabilizing viral peptides.…”
Section: Discussionmentioning
confidence: 99%
“…L2 is required for infectivity and required for egress of viral genomes from endosomes, while L1 does not appear to exit the endosomal compartment [12,13]. Following endosomal escape, L2 accompanies the viral DNA to the nucleus.…”
Section: Viral Entry In the Basal Cellsmentioning
confidence: 99%